LITERATURE REVIEW: PERBANDINGAN EFEKTIVITAS PLATELET RICH PLASMA (PRP) DENGAN ASAM HIALURONAT (HA) SEBAGAI TERAPI OSTEOARTHRITIS - Anzani, Bella Pratiwi (Politeknik Kesehatan Tanjung Karang, 2020)
The prevalence of osteoarthritis is increasing with age. In osteoarthritis, there is a change in the joint process that fails to repair damaged cartilages and manifestations such as joint narrowing, osteophytosis, subcondral sclerosis, and abnormal bone shape. Pharmacological therapies such as analgesics, corticosteroids, glucosamine, chondroitin sulfate, and non-steroidal anti-inflammatory drugs are used together with viscosupplementation to help and improve the development of arthritis. Intra-articular injection therapy is also used as a good choice for osteoarthritis therapy. Hyaluronic acid (HA) and platelet-rich plasma (PRP) are the two choices of intraarticular therapy that can be used. Hyaluronic acid can reshape cartilage through aggregation with proteoglycans and can improve synovial fluid present in the joints, but therapy with hyaluronic acid has a long-lasting, expensive, and proven effect. Platelet-rich plasma (PRP) is a new therapy. PRP is obtained from blood centrifugation several times. PRP is very easy to get, cheap and non-invasive. PRP contains various growth factors that can regenerate damaged cartilages. PRP can be applied and has the same benefits as HA, but until now there has been no consensus that which is a better outcome between the two therapies. From various literature it is known that PRP is more effective than hyaluronic acid as osteoarthritis therapy.